Public expenditure and growth: the Indian case - A. Bhatt Hakhu; Claudio Sardoni (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
The paper deals with the relationship between public spending and growth as well as the dynamics of the ratio of public debt to GDP. The authors show that a composition of public spending that favors productive expenditures, that is, those with a direct positive effect on the economy's long-run rate of growth, can determine a situation in which the ratio of public debt to GDP is stable, even though the government runs primary deficits. We test our theoretical results by considering the Indian case. Our empirical analysis substantially supports the idea that the dynamics of the economy as well as of the public-debt ratio are contingent on having a public sector that favors productive expenditures.
Keywords: H30; H54; H60; 330; public expenditure; growth; public debt